1973
DOI: 10.1111/j.1469-185x.1973.tb00980.x
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Ionic Concentrations in the Internal Media of Animals

Abstract: Summary 1. The electrical and ionic gradients across a cell membrane depend on its permeability properties, on the concentration and net valency of the organic constituents of the cytoplasm and on the critical energy barrier to the extrusion of sodium. Such considerations do not, however, explain the small extent to which the concentration of potassium varies in myoplasm which may, instead, be related to the effects of potassium on particular enzymes. 2. The fact that the apparent optimum level of potassium ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

1975
1975
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(7 citation statements)
references
References 155 publications
0
6
1
Order By: Relevance
“…It has been claimed that prolactin causes increased cell K+ concentration and decreased cell Na+ concentration in pseudopregnant and lactating rabbits (3,4). We note, though, that in these studies intracellular Na+ concentrations were well above 100 mM and similar to intracellular K+ concentrations; this situation is markedly different from that in most cells (30) and from that observed in guinea pig mammary glands in two earlier studies (31,32).…”
Section: Methodscontrasting
confidence: 82%
“…It has been claimed that prolactin causes increased cell K+ concentration and decreased cell Na+ concentration in pseudopregnant and lactating rabbits (3,4). We note, though, that in these studies intracellular Na+ concentrations were well above 100 mM and similar to intracellular K+ concentrations; this situation is markedly different from that in most cells (30) and from that observed in guinea pig mammary glands in two earlier studies (31,32).…”
Section: Methodscontrasting
confidence: 82%
“…Ionic regulation is the capacity of an organism to build up and maintain specific ionic gradients between body fluids and the cell fluids. The regulation of ionic composition of the body fluid is presumed to have adaptive significance for the organism (Burton 1973). Unfortunately, in today's world all the water resources such as lakes, ponds, rivers, sea etc.…”
Section: Introductionmentioning
confidence: 99%
“…have become a common damp yard for domestic sewage, exposure for oils, industrial chemicals, pesticides, metals etc. Investigations carried out by [1]-to [22] have shown that pesticide impair osmoregulatory ability in many aquatic forms. The ionic regulation studies contribute valuable information to the role of ions in the blood chemistry of aquatic animals.…”
Section: Introductionmentioning
confidence: 99%
“…The shell wall thickness ln the man-made reservoirs studied was not correlated with the calcium content in the habitat. This might have resulted from the fact that in living organisms the magnesium act antagonistically to the calcium ions, in competing for the same binding sites in the cell membrane (Burton 1973). An excess of magnesium probably reduces the •ability to use calcium during the shell formation, though the former element has never been found a shell co~ponent (Strzelec unpublished data).…”
Section: Discussionmentioning
confidence: 99%